BBC Science and Technology section - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The BBC (Science and Technology section) posts reports, based on its radio broadcasts, on a wide range of local experiences in applying ICTs for development. For example, ´Digital Destinations: From Dakar2Dhaka´ and